2022
DOI: 10.3390/jcm11051250
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Matrix Proteins in Breast Cancer

Abstract: The extracellular matrix is a structure composed of many molecules, including fibrillar (types I, II, III, V, XI, XXIV, XXVII) and non-fibrillar collagens (mainly basement membrane collagens: types IV, VIII, X), non-collagenous glycoproteins (elastin, laminin, fibronectin, thrombospondin, tenascin, osteopontin, osteonectin, entactin, periostin) embedded in a gel of negatively charged water-retaining glycosaminoglycans (GAGs) such as non-sulfated hyaluronic acid (HA) and sulfated GAGs which are linked to a core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 324 publications
(640 reference statements)
0
33
0
Order By: Relevance
“…Integrin β1 is also involved in in control of the ECM and epithelial differentiation as shown through the effect of the absence of integrin β1 impairing STAT5 signaling, causing epithelial cells to detach from the basement membrane [ 145 ]. In addition, laminin is also involved in organogenesis and early development processes, likely due to their interactions on the cell surface [ 145 ].…”
Section: Clinically Relevant Emt-suppressing Biomarkers and Their Reg...mentioning
confidence: 99%
“…Integrin β1 is also involved in in control of the ECM and epithelial differentiation as shown through the effect of the absence of integrin β1 impairing STAT5 signaling, causing epithelial cells to detach from the basement membrane [ 145 ]. In addition, laminin is also involved in organogenesis and early development processes, likely due to their interactions on the cell surface [ 145 ].…”
Section: Clinically Relevant Emt-suppressing Biomarkers and Their Reg...mentioning
confidence: 99%
“…We also observed down-regulation of FN1 transcript (−3.1 f.ch. ), which encodes preprotein fibronectin, a proteolytically processed glycoprotein involved in cell adhesion and migration processes, wound healing, and metastasis [ 32 ]. Cell cycle regulator CCND1 (cyclin D1) was also down-regulated (−3.2 f.ch.)…”
Section: Resultsmentioning
confidence: 99%
“…In a follow-up study, the Notch-regulated uPA–plasmin axis activates latent TGF-β in stroma cells [ 106 , 107 ], which stimulates the TGF-β receptor 1, another Notch target gene in BCs [ 95 ]. Several reports have recently revealed that the ECM proteins Periostin and Tenascin C play key roles as metastasis niche components for tumor-initiating cells that invade different organs [ 108 , 109 ]. By enhancing Wnt and Notch signaling in cancer cells, these proteins provide physical as well as signaling support for metastasis-initiating cells [ 110 ].…”
Section: Notch Signaling Regulates Bc Progressionmentioning
confidence: 99%